Implications of the Heat Generation of LMR-NCM on the Thermal Behavior of Large-Format Lithium-Ion Batteries. Issue 5 (27th May 2021) - Kraft, Ludwig; Hoefling, Alexander; Zünd, Tanja; Kunz, Alexander; Steinhardt, Marco; Tübke, Jens; Jossen, Andreas
Abstract : Lithium- and manganese-rich NCM (LMR-NCM) cathode active materials exhibit a pronounced energy inefficiency during charge and discharge that results in a strong heat generation during operation. The implications of such a heat generation are investigated for large-format lithium-ion batteries. Small laboratory cells are generally considered isothermal, but for larger cell formats this heat cannot be neglected. Therefore, the heat generation of LMR-NCM/graphite coin cells and NCA/graphite coin cells as a reference is measured for varying charge/discharge rates in an isothermal heat flow calorimeter and scaled to larger standardized cell formats. With the aid of thermal 3D models, the temperature evolution within these cell formats under different charge/discharge operations and cooling conditions is analyzed. Without an additional heat sink and any active cooling of larger LMR-NCM/graphite cells, discharge C-rates lower than C/2 are advisable to keep the cell temperature below a critical threshold. If the loads are increased, the cooling strategy has to be adapted to the specific cell format, otherwise critical temperatures above 60 °C are easily reached. For the investigated convective surface cooling and base plate cooling scenarios, thick prismatic cell formats with LMR-NCM are generally unfavorable, as the large amount of heat cannot be adequately dissipated.